Preventing erosion of oral polio vaccine acceptance: A role for vaccinator visits and social norms. Issue 27 (15th June 2022) - SteelFisher, Gillian K.; Caporello, Hannah; McIntosh, Ross; Muhammad Safdar, Rana; Desomer, Lieven; Chimenya, Dennis; Abdelwahab, Jalaa'; Ratna, Jalpa; Rutter, Paul; O'Reilly, Denise; Gilani, Bilal I.; Williams, Matthew R.; et al.
Abstract: Background: With continued challenges to the timeline for polio transmission interruption in Pakistan, including COVID-19, there is a risk of oral polio vaccine campaign fatigue among caregivers of young children. Renewed efforts to minimize oral polio vaccine acceptance erosion may be needed. This study examines the possible role of social norms in protecting against acceptance erosion and the role of vaccinators in promoting these social norms. Methods: Data were analyzed from a poll conducted by local interview teams between February 23 and April 5, 2016, among 4, 070 parents and other caregivers of children under age 5 living in areas at high-risk for polio transmission in Pakistan. The sample was drawn via a stratified multistage cluster design utilizing random route methods at the household level. We calculated the prevalence of subjective and descriptive social norms around vaccine acceptance; vaccine acceptance and commitment to vaccinate in future; and experiences and views of polio vaccinators across the population. We examined the relationship between these social norms and vaccination behaviors as well as the relationship between experiences with and views of vaccinators and social norms using uncontrolled comparisons (t-tests of proportion) and logistic repressions to control for demographics. Results: Both descriptive and subjective positive social norms were associated with vaccine acceptance and future commitment. Positive experiences with and views of vaccinators (trust, perceived technical knowledge, compassion, and overall pleasantness of the interaction) were associated with both descriptive and subjective positive social norms. Conclusions: These data support the idea that positive social norms could be protective against erosion of oral polio vaccine acceptance and that positive experiences with, and views of, vaccinators could help promote these positive social norms. Creative community engagement efforts may be able to leverage positive experiences with vaccinators to help foster social norms and protect against the risk of acceptance erosion.